Estudo do processo de cristalização de soluções impuras de sacarose por resfriamento - Mantelatto, Paulo Eduardo (Universidade Federal de São Carlos, 2005)
The objective of this work was to study the crystallization kinetics of impure sugarcane sucrose solutions by cooling, prepared as of VVHP and VHP raw sugars, sugarcane syrup and for PP-45 high purity granulated sugar (reference sample), as a part of technology development work for high purity sugar production. The applied methodology was that one proposes by Nývlt, which allows finding out the crystallization kinetics parameters without knowing solutions supersaturation coefficient figures. This method basically consists of submitting a saturated sucrose solution under a cooling linear slope until crystal uprising and their growth, which are separated from mother liquor, submitted to crystal size distribution analysis (for example crystal retained in sieves) to determine the distribution size curve (DSC) and finally, to submit math modeling. This way batch crystallization trial of sugarcane syrup and sucrose solutions with different impure degrees and concentration were carried out in all cases mentioned before, using or not crystal seeding. As of which this data, the predominant medium crystal size of DSC were determined (Lm), which permitted to find out crystallization kinetics parameters: the relationship between real nucleation order and growth rate (n/g), reactor kinetics constant (BN) and nucleation apparent order (m). The results showed a good correlation among evaluated parameters, for confidence intervals of 99,5%, with at least 90% of variation explained (correlation coefficient, r > 0,9). The equation found this way allowed to foresee with reasonable accuracy crystal predominant medium size for all studied cases. The best adjustment of proposed model was gotten for seeding syrup, VVHP raw sugar (obtained for seeding and nucleation), and VHP (by seeding) and for PP-45 granulated sugar, respectively. The worst results were for prepared solution as of VHP (I) raw sugar (by nucleation), which apparently, were influenced by high level of starch, dextran, and other impurities originally present in this raw sugar. The crystals obtained, in turn, presented an excellent coefficient of variation, C.V., between 6,9% (best case) and 28% (worst case), a flatness about 3,0, characterizing a type of normal distribution and showing to be a narrow distribution, specially for the case where seeding was applied. The process showed to be effective in impurities removal, specially starch, ash and mainly color compounds. The color of crystals obtained were classified as of sugar type 4 (450 UI), when syrup with 8600 UI was used and non affination was applied until refined type, with 18 UI of color, when VVHP row sugar (310 UI) was utilized, crystal with 56 UI when VHP(I) raw sugar (1040 UI) was used and crystal with 22 UI when VHP raw sugar with original color of 846 UI. The results suggest that refining of raw sugar could be done using an adequate cooling crystallization technique perfectly integrated to a conventional sugar factory utilized to produce VHP, VVHP and other types of crystal raw sugars. The refined sugar so produced could be adjusted in the adequate market proportion for each sugar type in the same plant utilized for conventional raw sugar production. This process so conceived or arranged could have a significant advantage when compared to the conventional refining sugar process since it would not need an ionic or carbon column to color and ash removal, no new chemicals would not be necessary, no new wastes would be generated, the process would became more flexible and more value could be added to the product. It has pointed out also that if the results here present are confirmed in the next pilot scale study the product should have besides a better acceptance in the international sugar market an expressive production cost reduction.
Keywords: Cristalização; Sacarose; Cana-de-açúcar; Purificação de açúcar; Engenharia Química; ENGENHARIAS::ENGENHARIA QUIMICA